The Effect of Liquidity, Solvency and Profitability Ratio on Financial Distress in Tourism Sector Companies Listed on the Indonesia Stock Exchange In The 2020-2022 Period - Setiabudhi, Hatta; Khumaidah, Nila; Suwono, Suwono (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
The impact of the Covid-19 pandemic has spread to many industries, including the tourism sector, which is the hardest hit sector in Indonesia. This study was conducted to determine the effect of the financial ratios of liquidity, solvency, and profitability on financial distress in tourism sector companies listed on the Indonesia Stock Exchange. The population in this study was 147 company financial reports. The sample determined through purposive sampling was obtained with a total of 105 samples. This type of research is explanatory research with a quantitative approach. The method used is logistic regression analysis using IBM SPSS 25. The results of the study show that partially the liquidity solvency ratio does not have a negative effect on financial distress, while partially the profitability ratio has a positive effect on financial distress. Simultaneously, the liquidity, solvency, and profitability ratios have an effect on financial distress.